2016
DOI: 10.1007/s00276-016-1783-x
|View full text |Cite
|
Sign up to set email alerts
|

Wrist denervation of the posterior interosseous nerve through a volar approach: a new technique with anatomical considerations

Abstract: This study shows the local anatomy of the PIN, allowing denervation via a volar approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…On deep dissection to the anterior distal forearm, care must be taken not to damage branches of the AIN, especially when working around PQ. The AIN was shown to be located some distance from the RS, 6.67 cm (±0.92) and 5.5 cm (±0.6) as reported by Grechenig et al (2017) and Hinds et al (2015), respectively. However, during procedures involving mobilization of the PQ, the surgeon must be aware that branches of AIN may be located 1.7 cm distal from the distal PQ border (Hinds et al, 2015).…”
Section: Safe and At-risk Zones In The Anterior Approach To The Dista...mentioning
confidence: 75%
See 2 more Smart Citations
“…On deep dissection to the anterior distal forearm, care must be taken not to damage branches of the AIN, especially when working around PQ. The AIN was shown to be located some distance from the RS, 6.67 cm (±0.92) and 5.5 cm (±0.6) as reported by Grechenig et al (2017) and Hinds et al (2015), respectively. However, during procedures involving mobilization of the PQ, the surgeon must be aware that branches of AIN may be located 1.7 cm distal from the distal PQ border (Hinds et al, 2015).…”
Section: Safe and At-risk Zones In The Anterior Approach To The Dista...mentioning
confidence: 75%
“…The mean anterior-posterior distance was 0.28 cm (±0.02) between the two nerves. Grechenig et al (2017) showed these nerves were closest to one another at 8 cm proximal to the RS and a mean 0.84 cm (±0.23) from the ulnar edge of the radius. Jariwala et al (2014) highlighted in their study the proximity of the last motor branch of the PIN to the ulnar head (4.7 cm ± 0.84) and showed the last motor branch of the PIN supplied the extensor indicis in 70% of cases and extensor pollicis longus (EPL) in 30%.…”
Section: Posterior Interosseous Nervementioning
confidence: 93%
See 1 more Smart Citation
“…It is unclear whether this procedure improves outcomes because of denervation of the radiocarpal joint and helps resolve other pathology, or PIN neurectomy denervates the DRUJ. [26][27][28] It is also possible the PIN neurectomy is a surrogate for other technical factors that are unable to be captured in the data available.…”
Section: Discussionmentioning
confidence: 99%
“…Denervation techniques of the wrist have been modified over the years from Wilhelm’s ‘complete’ denervation in 1959 (Wilhelm, 2001) to less invasive ‘partial’ denervation using only a single incision (Berger, 1998; Grechenig et al., 2017). Partial denervation focuses on specific articular nerves, especially the anterior interosseous nerve (AIN) and posterior interosseous nerve (PIN).…”
Section: Introductionmentioning
confidence: 99%